Analysis Symmetrical Blade Propeller Performance for Jalapatih 3 Ship Using CFD - Edi Jadmiko; Tony Bambang Musriyadi; Abdi Sauqi Akram (International Journal of Marine Engineering Innovation and Research, 2020)
Solar Sport One is a prestigious competition held annually in the Netherlands. The competition focuses on innovation, technology, and sustainable energy. Based on the experience/participation of Marine Solar Boat Team (MSBT) ITS in Event Solar Sport One 2018 using Jalapatih 3 vessel, then researched the propulsion system especially propeller for use in the next Solar Sport One event. This paper is done research using an opensource program called Openprop to design a propeller using numerical calculations for the ship Jalapatih 3. The research is conducted in several phases, where our initial stage of designing and counting numerically uses Openprop and comparing the calculation results with CFD simulation results as Performance analysis of the selected propeller. From a propeller model that has been designed, Fortescue Blade Propeller has not been able to push the ship Jalapatih 3 at 16 knots and the result of the comparison, gained the difference of Thrust J = 1.4 of 22.063 N while Torque value has a difference of 2.35 Nm.